Faktor Penentu Corporate Cash Holding Perusahaan Manufaktur Di Bei - Calvina Calvina; Ignatius Roni Setyawan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
The purpose of this study is examined corporate cash holding determinants of manufacturing firms in Indonesia Stock Exchange for the period 2015-2017. Factors identified in the literature that determine corporate cash holding, including growth opportunity, leverage, cash flow volatility, capital expenditure, and corporate governance, are examined in this study. The samples included 81 manufacturing companies was selected using the purposive sampling technique. Generalized Least Square estimation based on fixed effect model were applied to test the hypothesis. Leverage and capital expenditure are found to have negative and significant impact toward corporate cash holding. While growth opportunity, cash flow volatility, and corporate governance with board independence as its proxy is found to have positive and significant impact to corporate cash holding. Tujuan dari penelitian ini adalah menguji faktor penentu corporate cash holding perusahaan manufaktur di Bursa Efek Indonesia pada periode 2015-2017. Faktor yang diidentifikasi dalam literatur yang menentukan cash holding perusahaan termasuk growth opportunity, leverage, cash flow volatility, capital expenditure, dan corporate governance diuji dalam penelitian ini. Sampel penelitian termasuk 81 perusahaan manufaktur dipilih berdasarkan teknik purposive sampling. Estimasi Generalized Least Square berdasarkan model fixed effect diterapkan untuk menguji hipotesis. Hasil penelitian menunjukkan bahwa leverage dan capital expenditure berpengaruh secara signifikan dan negatif terhadap corporate cash holding. Serta growth opportunity, cash flow volatility, dan corporate governance dengan pengukuran board independence berpengaruh secara signifikan dan positif terhadap cash holding.